Composting as a Strategy for Biodegradable Marine Debris Reduction and Management in Jakarta - Mega Mutiara Sari; Takanobu Inoue; Regil Kentaurus Harryes; Kuriko Yokota; Iva Yenis Septiariva; Sapta Suhardono; Shigeru Kato; Suprihanto Notodarmojo; I Wayan Koko Suryawan (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2024)
This study explores the potential for managing biodegradable marine debris waste in Jakarta City through composting, aiming to reduce and treat this waste effectively. In Jakarta, river debris predominantly consists of materials that degrade easily and are biodegradable. Composting represents the most straightforward method for processing this type of organic waste. The study's objective was to evaluate the feasibility of composting organic biodegradable river debris as a waste management strategy. Data collection was conducted at Emplacement Pluit, utilizing random sampling with the four quadrants method. Out of the total river debris generated daily, which amounts to 309 m³, approximately 9.07 m³/day was found suitable for composting. The composting process resulted in a significant reduction of river debris volume by 50.15% within a 30-day detention period. This process was facilitated by mesophilic microbial activity at temperatures between 30-38°C. During the first two weeks, the composting environment remained acidic until the pH stabilized to a normal range between 6.8 and 7.49. A notable observation was the high initial water content of the river debris, recorded at 53.846%, which only reduced to 42.857% by the end of the 30-day decomposition period. Therefore, a pretreatment step is recommended to optimize the water content before composting. Despite these challenges, the compost produced met the required standards set by SNI 19-7030-2004. This study underscores the importance of managing biodegradable organic waste at its source to alleviate the burden on landfills, which are currently operating beyond their capacity.